0588 Ring Pulse Oximeter for Screening of Moderate to Severe OSA: A Pilot Study. (27th May 2020) - Xue, J; Zhao, R; Li, J; Zhao, L; Zhou, B; Dong, X; Han, F
Abstract: Introduction: To evaluate the utility of the ring pulse oximeter for screening of OSA in adults. Methods: 87 adults were monitored by a ring pulse oximeter and PSG simultaneously during a nocturnal in-lab sleep testing. 3% oxygen desaturation index (ODI3 ); Mean oxygen saturation(MSpO2 ), Saturation impair time below 90% (SIT90) derived from an automated algorithm of the ring pulse oximeter. Meanwhile, the parameters of PSG were scored manually according to the AASM Manual. Correlation and receiver operator characteristic curve analysis were used to measure the accuracy of ring pulse oximeter and its diagnostic value for moderate to severe OSA (AHI≥15). Results: Among the 87 participants, 18 cases were AHI<5, 17 cases were diagnosed with mild OSA (AHI:5-14.9), 25 cases were diagnosed with moderate OSA (AHI:15-29.9) and 27 cases were diagnosed with severe OSA (AHI≥30). There was no significant difference between PSG and ring pulse oximeter in regard to ODI3 (23.4±23.5 vs 24.7 ± 21.7), and SIT90 (1.54%, range 0.14%-8.99% vs. 3.20%, range 0.60%, 12.30%) (P>0.05], Further analysis indicated that two parameters from the oximeter correlated well with that derived from PSG (r=0.889, 0.567, respectively, both p<0.05). Although MSpO2 correlated significantly (r=0.448, P<0.05), the difference was remarkable [95.9%, range 94.0% to 97.0% vs. 94.5%, range 93.3% to 95.7%, p<0.05]. Bland-Altman plots showed that the agreement of these three parameters was within the clinical acceptance range. The ROC curve showed that the sensitivity and specificity of the ring pulse oximeter when the oximeter derived ODI3 ≥12.5 in the diagnosis of moderate to severe OSA were 82.7% and 74.3%, respectively. Conclusion: The pilot study indicated that ring pulse oximeter can detect oxygen desaturation events accurately, therefore to be used as a screening tool for moderate to severe OSA. Support: The study was supported by the National Natural Science Foundation of China (No. 81420108002 and NO. 81570083).